2010
DOI: 10.1002/macp.201000245
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Polysulfones by Click Chemistry

Abstract: Functionalization of polysulfones by using “Click” chemistry is described for the example of a small fluorescent analyte propargylpyrene. First, PSUs were converted to azido‐functionalized polymers by successive chloromethylation and azidation. Propargylpyrene was prepared independently as a fluorescent click component. Finally, the azido‐functionalized PSUs were coupled with propargylpyrene with high efficiency by copper‐catalyzed azide/alkyne click reactions. The final polymers and intermediates at various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 67 publications
5
49
0
Order By: Relevance
“…[33,34] Many examples of click reactions involving macromolecules were reported. In this laboratory, we have focused on the use of such click reactions for the synthesis of various macromolecular architectures [34][35][36][37][38][39][40][41] and functionalization of polymers [42][43][44][45][46][47], microspheres [48], clays [49,50], and silsesquioxanes [51] with thermal-, photo-, and electro-active groups.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] Many examples of click reactions involving macromolecules were reported. In this laboratory, we have focused on the use of such click reactions for the synthesis of various macromolecular architectures [34][35][36][37][38][39][40][41] and functionalization of polymers [42][43][44][45][46][47], microspheres [48], clays [49,50], and silsesquioxanes [51] with thermal-, photo-, and electro-active groups.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] PSUs have also been successfully functionalized with Py by successive chloromethylation, azidation, and click chemistry processes (Scheme 1). [23] Click chemistry has been reported as a promising approach for the construction of various bioconjugates, biomaterials as well as functional bioactive surfaces. [24] In a previous work, [23] we demonstrated that PSUs can be successfully post-functionalized by using click chemistry on the example of fluorescent Py molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Click chemistry has been reported as a promising approach for the construction of various bioconjugates, biomaterials as well as functional bioactive surfaces. [24] In a previous work, [23] we demonstrated that PSUs can be successfully post-functionalized by using click chemistry on the example of fluorescent Py molecule. It was considered that incorporation of such molecules might bring remarkable fluorescence regulated behavior when subjected to irradiation which makes them useful candidates for various applications in biomolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The copper-catalyzed click reactions, Diels-Alder reactions, and thiol-ene reactions are such click reactions with very high yields and nearly no by-product formation. Recently, the ketene chemistry is also announced as a promising route for the modification of macromolecular structures with significant yields.…”
mentioning
confidence: 99%